Anteseden Repurchase Intention Pada Produk Batik Di Indonesia (Fakultas Ekonomi Universitas Gresik, 2023)
This study examines Anteseden Repurchase Intention on batik products in Indonesia, Social media marketing activities, brand awerness, ewom, and purchase intention. This study used primary data obtained through an online questionnaire from one hundred and forty (170) respondents. Social media customers are hired for quantitative studies through convenience sampling. Data were analyzed using the Structural Equation Model (SEM) using the SPSS and Amos programs. The results of this study show that brand awerness does not have a positive effect on Repurchase intention, while Social media marketing, electronic word of mouth has a positive effect on repurchase on social media.